A Bibliometric Analysis of Drinking Water Management on an Island using Vosviewer - Vendhy Vendhy; Andri Irfan Rifai; Amanatullah Savitri (CV. Syntax Corporation Indonesia, 2024)
The availability of safe and clean drinking water is one of the most basic human rights that is essential for the sustainability of life for public health. Without drinking water, life as we know it today would not be possible. The main objective of this research is to conduct a bibliometric analysis in order to better understand the current knowledge and direction of research in drinking water management. This research used bibliometric analysis with VOSviewer software to investigate drinking water management. The research centered on journals indexed in Semantic Scholar, using keywords such as drinking water management, water resources, and water quality, with a maximum of 1000 results from 2000 - 2023. In the network visualization analysis, “groundwater quality” had the highest total link strength of 141 and 107 occurrences, making it the densest color. In particular, the year 2018 had the highest number of publications, with a total of 72 publications. Regarding citations, the peak occurred in 2019, with a significant number of 3930. India emerged as the country with the highest volume of research on drinking water, contributing 66 publications.